Etude de l’activité anti bactérienne du miel de Ziziphys lotus. L sur les infections intestinales - ABBASSA, BATOUL; CHACHOU, SOFIANE (My University, 2023)
Honey is the miraculous ingredient that has baffled scientists due to its composition and how it is produced by bees. Honey has many therapeutic properties, including eliminating bacteria and resulting infections. This study was conducted to know the effect of Ziziphus lotus honey on the intestinal infection caused by Escherichia coli, we obtained zones of inhibition from 8 to 43 mm by following the Well Method and with different concentrations of honey (100%, 50%, 25%, 12.5%, 6.25%). We obtained zones of inhibition from 10 to 45 mm by following the disc method. And we obtained a pourcentage of inhibition from 35% to 98% in the method of spectrophotometry. We note that the spectrophotometric method is the most accurate. The study conducted proved that Ziziphus lotus honey is effective in eliminating intestinal infections caused by Escherichia coli bacteria.
Keywords: Honey Ziziphus lotus Escherichia coli Intestinal infections